Trends in Care Practices, Morbidity, and Mortality of Extremely Preterm Neonates, 1993–2012. Issue 1 (January 2016) - Stoll, Barbara J.; Hansen, Nellie I.; Bell, Edward F.; Walsh, Michele C.; Carlo, Waldemar A.; Shankaran, Seetha; Laptook, Abbot R.; Sánchez, Pablo J.; Van Meurs, Krisa P.; Wyckoff, Myra; Das, Abhik; Hale, Ellen C.; et al.
Abstract : Obstet Gynecol Surv 2016;71(1):7–9 Since the 1990s, there have been considerable changes in care for mothers in preterm labor and for extremely preterm infants. The Eunice Kennedy Shriver National Institute of Child Health and Human Development Neonatal Research Network has monitored changes in this care for more than 2 decades and, most recently, evaluated data from 2003 to 2007.